Otolaryngology exposure in a longitudinal integrated clerkship setting - Grace Margaret Scott; Corliss Ann Elizabeth Best; Damian Christopher Micomonaco (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Although 20–40% of primary care complaints are Otolaryngology-Head and Neck Surgery (OtoHNS) related, little emphasis is placed on OtoHNS instruction at the undergraduate medical education level. An OtoHNS clerkship rotation is not required at most Canadian medical schools. Furthermore, at institutions offering an OtoHNS rotation, less than 20% of students are able to complete a placement. Given that a large percentage of medical students in Canada will pursue primary care as a career, there remains a gap in providing OtoHNS clinical training. During the longitudinal integrated clerkship at the Northern Ontario School of Medicine (NOSM), students are assigned to one of 14 sites, and not all have access to an otolaryngologist. This study looks to quantify the level of exposure students are receiving in OtoHNS at NOSM and to assess their comfort level with diagnosing and treating common otolaryngologic conditions. Methods A structured 13-item survey was administered to second, third and fourth year medical students at NOSM. Results A majority (67.9%) of medical students surveyed had not observed an otolaryngologist. Furthermore, most students (90.6%) reported receiving very little OtoHNS classroom based and clinical instruction during medical school. Conclusions A discrepancy exists between the quantity and breadth of OtoHNS training received in undergraduate medical education and the volume of OtoHNS encounters in primary care practice. Although geographic dissemination of students in the distributed learning model may be a challenge, strategies such as standardized objectives and supplemental electronic resources may serve to solidify clinical knowledge.